CASSIA ESSENTIAL OIL: EFFECTIVE ANTICANDIDAL AND POSSIBLE THERAPEUTIC AGENT - VILAS A. KAMBLE (International Journal of Pharma and Bio Sciences, 2014)
The antimicrobial property of volatile aromatic oils from medicinal as well as other edible plants has been recognized since antiquity. Candida species are an important cause of opportunistic infections in the oral cavity of immunocompromised patients and vaginal candidiasis. The antifungal activity of the essential oil of Cinnamomum cassia (cassia oil) was investigated against 75 clinical isolates of Candida albicans and non-albicans Candida. Disc diffusion method was used to evaluate the sensitivity profile of clinical isolates to undiluted and diluted (3:1, 2:2 and (1:3) cassia oil. Minimum inhibitory concentrations (MIC) and minimum fungicidal concentrations (MFC) were evaluated by broth microdilution and broth macrodilution method. . Cassia essential oil strongly inhibited all clinical isolates of C. albicans and non-albicans Candida with growth inhibition zones ranging from 40 to 72 mm. Cassia oil inhibited C. albicans growth with mean minimum inhibitory concentration (MIC) of 0.10 µl/ml (v/v) and 0.07 µl/ml (v/v) by broth micro dilution and broth macrodilution method, respectively. The clinical isolates of C. albicans required as high as 0.15 µl/ml (v/v) concentration of cassia oil for its inhibition by both methods. The isolates of nonalbicans Candida showed MIC range of 0.02 – 0.62 µl/ml (v/v) by broth microdilution and broth macrodilution method.